Intelligence Differences and Mediation Factors: A Sequential Explanatory Study of Improvement of EFL Undergraduate Students’ Reading Comprehension Skills - Celik, Suleyman (Universitas Negeri Makassar, 2019)
In this quasi-experimental study, quantitative findings were examined in terms of how grouping students based on their dominant type of Multiple intelligence and providing different Multiple Intelligence activities that correspond to their intelligence type effect the development of their reading skills. A control group and an experimental group were designed to compare the effectiveness of the Multiple Intelligence teaching activities and tasks on the development of reading skills. A questionnaire was administrated to the 95 undergraduate EFL junior students to identify their dominant type of intelligence at a private university in Iraq. Based on their dominant type of intelligence, different learning centers were established with different activities for each one. After a 16-week experiment period the effects of Multiple Intelligence teaching activities were measured by using pretest, progress tests, achievement exams and a posttest. The results of this study indicated that the experimental group has significantly developed their reading comprehension skills in terms of understanding and visualizing the meaning in the mind. In addition, there were considerable association between Multiple Intelligence teaching activities and students’ motivation to the classes that reinforces classroom management as well.